α-Glucosidase inhibitors boost gut immunity by inducing IgA responses in Peyer’s patches - Hattori-Muroi, Kisara; Naganawa-Asaoka, Hanako; Kabumoto, Yuma; Tsukamoto, Kei; Fujisaki, Yosuke; Fujimura, Yumiko; Komiyama, Seiga; Kinashi, Yusuke; Kato, Miki; Sato, Shintaro; Takahashi, Daisuke; Hase, Koji (Frontiers in Immunology, 2023)
Peyer’s patches (PPs) are specialized gut-associated lymphoid tissues that initiate follicular helper T (Tfh)-mediated immunoglobulin A (IgA) response to luminal antigens derived from commensal symbionts, pathobionts, and dietary sources. IgA-producing B cells migrate from PPs to the small intestinal lamina propria and secrete IgA across the epithelium, modulating the ecological balance of the commensal microbiota and neutralizing pathogenic microorganisms. α-glucosidase inhibitors (α-GIs) are antidiabetic drugs that inhibit carbohydrate digestion in the small intestinal epithelium, leading to alterations in the commensal microbiota composition and metabolic activity. The commensal microbiota and IgA responses exhibit bidirectional interactions that modulate intestinal homeostasis and immunity. However, the effect of α-GIs on the intestinal IgA response remains unclear. We investigated whether α-GIs affect IgA responses by administering voglibose and acarbose to mice via drinking water. We analyzed Tfh cells, germinal center (GC) B cells, and IgA-producing B cells in PPs by flow cytometry. We also assessed pathogen-specific IgA responses. We discovered that voglibose and acarbose induced Tfh cells, GCB cells, and IgA-producing B cells in the PPs of the proximal small intestine in mice. This effect was attributed to the modification of the microbiota rather than a shortage of monosaccharides. Furthermore, voglibose enhanced secretory IgA (S-IgA) production against attenuated Salmonella Typhimurium. Our findings reveal a novel mechanism by which α-GIs augment antigen-specific IgA responses by stimulating Tfh-GCB responses in PPs, and suggest a potential therapeutic application as an adjuvant for augmenting mucosal vaccines.